Effects of temperature and food quality on age and size at maturity in ectotherms: an experimental test with Atlantic salmon. (20th August 2012) - Jonsson, Bror; Jonsson, Nina; Finstad, Anders G.; Genner, Martin
Summary The reaction norm between growth rate, age and size at maturity in ectotherms is widely debated in ecological literature. It has been proposed that the effect depends on whether growth is affected by food quality or temperature (called the Berrigan–Charnov puzzle). The present experiment tested this for Atlantic salmon (Salmo salar). We enhanced growth rates by increasing temperature and ratio of lipids to proteins in the food for groups of Atlantic salmon. Both treatments gave higher percentages of early mature and therefore smaller adults in contrast to the proposed Berrigan–Charnov puzzle. There was a difference between sexes in that males could attain maturity 1 year younger than females when reared under similar environmental conditions. Males that matured during the first year in sea water were smaller than similar aged immature males. The probability of that Atlantic salmon attained maturity for the first time during their second year in sea increased with growth rate during the preceding winter and if fed a high‐lipid diet. Increased summer temperature exhibited no additional effect. Similar aged fish reared at elevated temperature and fed high‐lipid diet attained maturity at a larger body mass and exhibited higher mass‐length‐ratios than those reared at natural temperature and fed a low‐lipid diet, indicating that structural growth has priority over lipid deposits. Increased growth rate before the onset of maturation, whether this is owing to enhanced lipid content in food or increased water temperature, decreased age and therefore size at maturity. Enhanced lipid relative to protein content in food, but not temperature, had an additive positive effect on early maturation probability, likely due to increased amounts of reserve energy. These results may be general for ectotherm organisms.